18.73% efficient and stable inverted organic photovoltaics featuring a hybrid hole-extraction layer. Issue 4 (14th February 2023) - Lin, Yuanbao; Zhang, Yadong; Magomedov, Artiom; Gkogkosi, Eleftheria; Zhang, Junxiang; Zheng, Xiaopeng; El-Labban, Abdulrahman; Barlow, Stephen; Getautis, Vytautas; Wang, Ergang; Tsetseris, Leonidas; Marder, Seth R; et al.
Abstract : Developing efficient and stable organic photovoltaics (OPVs) is crucial for the technology's commercial success. Abstract : Developing efficient and stable organic photovoltaics (OPVs) is crucial for the technology's commercial success. However, combining these key attributes remains challenging. Herein, we incorporate the small molecule 2-((3, 6-dibromo-9 H -carbazol-9-yl)ethyl)phosphonic acid (Br-2PACz) between the bulk-heterojunction (BHJ) and a 7 nm-thin layer of MoO3 in inverted OPVs, and study its effects on the cell performance. We find that the Br-2PACz/MoO3 hole-extraction layer (HEL) boosts the cell's power conversion efficiency (PCE) from 17.36% to 18.73% (uncertified), making them the most efficient inverted OPVs to date. The factors responsible for this improvement include enhanced charge transport, reduced carrier recombination, and favourable vertical phase separation of donor and acceptor components in the BHJ. The Br-2PACz/MoO3 -based OPVs exhibit higher operational stability under continuous illumination and thermal annealing (80 °C). The T 80 lifetime of OPVs featuring Br-2PACz/MoO3 – taken as the time over which the cell's PCE reduces to 80% of its initial value – increases compared to MoO3 -only cells from 297 to 615 h upon illumination and from 731 to 1064 h upon continuous heating. Elemental analysis of the BHJs reveals the enhanced stability to originate from the partially suppressed diffusion of Mo ions into the BHJ and the favourable distribution of the donor and acceptor components induced by the Br-2PACz.